Disaster and Migration: Lessons from the Irish Potato Famine (1845–52) - Kaplan, Robert S. (Tufts Archival Research Center, 2022)
Natural disasters are increasing in frequency and intensity due to climate change. However, migrant self-selection and assimilation following natural disasters are not yet well understood. Using recently digitized records from a 19th century savings bank in New York City, I examine how Irish immigrant self-selection and assimilation changed following the onset of the Irish Potato Famine, an ecological disaster during the Age of Mass Migration. In a difference-in-differences setting, I find that Famine-era Irish immigrant depositors are more negatively selected on wealth and human capital than the pre-Famine Irish. However, differences at arrival dissipate over time in terms of savings, geographic mobility, and upward occupational mobility. Among the Irish, I find that Famine-era depositors born in more Famine-afflicted regions are more negatively selected than less afflicted regions. These differences also dissipate over time. These results challenge historical views regarding Famine-era Irish immigrant socioeconomic status and provide new evidence on the consequences of natural disasters for migrant self-selection and assimilation.; Thesis (B.A.)--Tufts University, 2022.; Submitted to the Dept. of Economics.